Administrative suspension of operations for violations of industrial safety: theoretical and practical issues - M. A. Buchakova; M. D. Vershilo (Правоприменение)
The subject. The main issues of law enforcement activity on the application of administrative punishment in the form of administrative suspension of operations for identified offenses in the field of industrial safety of hazardous production facilities.The purpose of the article is to confirm or disprove hypothesis that Russian legislation allows the resumption of activities after the expiration of the period of its suspension without eliminating violations of industrial safety.The methodology of research is logical analysis of Russian legislation, statistical data and judicial decisions concerning enforcement of administrative suspension of operations in Russia.The main results. There is an ambiguous approach in the scientific literature to fixing the administrative suspension of operations in the system of administrative penalties. The effectiveness of its application is noted by some authors. At the same time, there are adverse consequences associated with the application of administrative suspension of operations for the further production activities of economic entities. Social tension in the collective of enterprises, difficulties of recovery after forced downtime, unclear prospects for further economic activity – this is not a complete list of problems arising in connection with the administrative suspension of activity. When making a court decision, judges often appoint a fine as a penalty and rarely a penalty in the form of suspension of operations. This is due to the complexity of the actual realization of suspension of operations, the special social significance of objects; the lack of a specialist's conclusion about the real danger of an offense. But if violations of industrial safety are detected during the operation of hazardous production facilities, it is initially possible to assume a high probability of serious consequences for the life and health of people, the environmental safety. Administrative suspension of activities is carried out by both judicial and non-judicial control authorities. In authors’ opinion, the application of this type of administrative punishment should be exclusively in the judicial jurisdiction. The law enforcement judicial practice concerning administrative suspension of operations in Russia is not uniform.Conclusions. There is a legal uncertainty in the mechanism of imposing administrative punishment in the form of administrative suspension of operations for violations of industrial safety of hazardous production facilities (Article 9.1 of the Russian Code of Administrative Offences). The uncertainty is manifested in the fact that the economic entity does not always eliminate the detected violations within the legally established period and after the expiration of the period for which the activity was suspended, the company resumes its activities nevertheless. Such opportunity reduces the preventive value of this punishment.